Usage of communication skills by midwives and its relation to clients' satisfaction - Taghizadeh Z; Rezaiepour A; Mehran A; Alimoradi Z (Tehran University of Medical Sciences, 2006)
Background & Aim: Because of importance of communication and its defects which has been observed in communication with clients, this study has been planned and done with the aim of investigation of usage of' communication skills by midwives and its relation to client's satisfaction. Methods & Materials: In a correlational study 50 midwives and 400 clients were investigated. Data collection method included observing midwife- client encounter using a checklist and interviewing clients to fill out satisfaction questionnaire. Descriptive and inferential statistics included chi- square test, fisher's exact test and Pearson correlation (p<0/05) were used for data analysis. Results: The results of this study showed that midwives' communication skills (verbal and non- verbal) was undesirable (62% and 56%). There was no relation between demographic variables and midwives' communication skills application. Just there was a relation between marital status and non-verbal communication skills application. Also clients' satisfaction with midwives' verbal and non-verbal communication skills (50% and 48/4%) was related meaningfully to midwives' communication skills application. There was a relation between clients' satisfaction and their age, educational status service they needed. Conclusion: According to undesirable usage of communication skills by midwives, administering interim training programs for midwives is recommended. Also it seems better to include communication skills training to midwifery curriculum.